Ergonomic Intervention on Physical Therapy Programs Decrease Pain and Disability Level on Subject with Myogenic Low Back Pain: A Case Report - I Made Dhita Prianthara; Ida Ayu Astiti Suadnyana; Komang Tri Adi Suparwati; Siti Ainun Marufa (Universitas Udayana dan Diaspora Taipei Medical University, 2021)
Introduction: Myogenic Low Back Pain is an uncomfortable pain on the lower back, often caused by musculoskeletal disorders resulting in pain and disability. This case report aims to review ergonomic intervention on physical therapy program on myogenic low back pain. Case description: A 45-years-old man working as a roof tile craftsman complained of pain in the lower back area and already felt it for 1 month ago. The pain did not radiate to the leg. The patient has no neurological signs and symptoms. Patient-reported that he had experienced the same incident about 9 times in the last 3 years ago. The patient always performed bending motion and lifting the roof tile every day. The patient has been visited physical therapy and received ergonomic intervention and physical therapy programs such as core stability exercise, soft tissue mobilization and modalities for seven weeks. Following the ergonomic intervention and therapeutic exercise application, the Visual Analogue Scale score decreased from 6 to 0. The Modified Oswestry Disability Index score gradually decreased from 60% disability to 0% disability. The patient no longer complained of MLBP and was able to lift the roof tile well. Conclusion: After a seven-weeks physical therapy treatment session, the patient did not feel pain and can perform forward bending. Modified Oswestry Disability Index score improved and demonstrated improved lifting the roof tile without any complaints. We concluded that the ergonomic intervention combined with physical therapy programs effectively decreased pain and disability level on a subject with MLBP